A case control study on obstetric outcome following a previous spontaneous abortion - Jayakumar, Sai Priya Remadevi; Jacob, Elizabeth; Somanathan, Rajani; Kanagasabhapathy, Karen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Spontaneous abortion is pregnancy resulting in miscarriages without the application of any deliberate methods to terminate it, during the early weeks after conception. Studies on effects of recurrent miscarriages on subsequent reproductive adverse outcomes are many in literature. However, studies showing outcome of pregnancy following a spontaneous complete abortion is scanty in literature.This study looks for association between a previous spontaneous abortion and recurrence of adverse maternal outcome like recurrence of abortion, preeclampsia, premature rupture of membrane (PROM), operative delivery, and fetal outcome like preterm labour (PTL), low birth weight (LBW) to that of primi gravida. Methods: A case control observational study was done on 200 antenatal women who attended the obstetrics department and fulfilling the inclusion criteria. Of this, 100 pregnant women were with history of a spontaneous abortion (case group) and 100 primi gravida (control group). Maternal and fetal adverse outcome were compared between the two groups. Results: Recurrence of adverse maternal outcome like recurrence of abortion, PROM, caesarean delivery and adverse fetal outcome like PTL, LBW were more in women with prior spontaneous abortion than that of primi gravida. Conclusions: Women with a history of previous one spontaneous abortion are at an increased risk of maternal and fetal complications. So, these women should be considered as high-risk group and hence frequent antenatal visits and close antenatal surveillance should be provided to such women for early detection of complications and for its effective management.